STUDENT ATTENDANCE REPORT SYSTEM CONTROLLED BY RADIO FREQUENCY IDENTIFICATION - Syarifah Idyan Syafiqah, Syed Hashim (Universiti Malaysia Sarawak, (UNIMAS), 2015)
This project will develop a student attendance system for Faculty of Computer Science and Information Technology (FCSIT) known as Student Attendance Report System Controlled by Radio Frequency Identification (RFID). This system aims to help lecturers to monitor the student's attendance. Since then, various initiatives have been implemented to support the Student Attendance Report System Controlled by Radio Frequency Identification. Furthermore it will also leveraging on the technology to improve the management processes within the organization. This project will develop a system for the FCSIT that known as Student Attendance Report System Controlled by Radio Frequency Identification. It will also provide updated information of the student attendance and will ease lecturer to taking student attendance.